Grain boundary relaxation behavior and phase stability of AlCrTiVx (x = 0, 0.5 and 1) high-entropy alloys. (November 2021) - Sun, Meng; Liu, Xueqing; Jiang, Weibin; Lei, Yawei; Ke, Jiangang; Liu, Rui; Wang, Xianping; Wu, Xuebang; Fang, Qianfeng; Liu, Changsong
Abstract: The defect relaxation behavior of AlCrTiV x ( x  = 0, 0.5, and 1) high entropy alloys was reported in this paper. A pronounced internal friction (IF) peak superimposing on a monotonously increasing high-temperature background (HTBG) was observed in all samples, which was ascribed to grain boundary peak. The activation energy of grain boundary relaxation increases with the increasing V content, implying an increasing complexity and difficulty of atomic diffusion with the increasing mixing entropy. After annealing at 1100 °C for 5 h, the HTBG of AlCrTiV alloy abnormally increases, which was attributed to the appearance of misfit dislocations induced by precipitation of nano-sized Ti-rich phases as confirmed by microstructure analysis. These findings may provide a new degree of freedom for evaluating and designing high entropy alloys with high thermal stability. Graphical abstract: Image, graphical abstract